The Role of Tuan Guru and Traditional Institutions in Shaping Religious Moderation Among the Sasak Community - baiq_mulianah (Universitas Islam Negeri (UIN) Mataram, 2024)
Sasak, the indigenous community of Lombok, possesses a unique social and cultural structure, where the role of Tuan Guru as Islamic religious figures is central to the formation of their religious and social identity. This article examines the role of Tuan Guru and traditional institutions in shaping the understanding of religious moderation among the Sasak community. Through a qualitative approach, this research explores how the Islamization process carried out by Tuan Guru integrates with local customs, creating a harmonious and moderate social order. The study finds that the preaching strategy of Tuan Guru, which emphasizes Islamic values with a contextual approach, has successfully internalized religious teachings into Sasak cultural practices. Additionally, Sasak proverbs function as effective educational media in instilling Islamic values. However, amid the challenges of modernization and globalization, the cultural and religious identity of the Sasak community remains preserved through the role of Tuan Guru and traditional institutions.